Final Height and Associated Factors in Perinatally HIV-infected Asian Adolescents - Bunupuradah T. (2017)
© 2015 Wolters Kluwer Health, Inc. We analyzed final height of 273 perinatally HIV-infected Asian adolescents older than 18 years at their last clinic visit. By the World Health Organization child growth reference, 30% were stunted, but by the Thai child growth reference, 19% were stunted. Half of those who were stunted at antiretroviral therapy initiation remained stunted over time. Being male and having a low baseline height-for-age Z score of less than-1.0 were associated with low final height Z score.